Analysis of the status and factors influencing physical activity in patients undergoing ovarian cancer chemotherapy - Zhang, Shasha; Zhang, Fengzhi; Yang, Fangfang; Yang, Jimei; Zhang, Lin; Xie, Junfang (Frontiers in Oncology, 2023)
Background Ovarian cancer is a common gynecological malignancy, leading to approximately 200,000 deaths globally in 2020. Research has shown that regular physical activity can reduce the toxic side effects of cancer treatment, reduce morbidity and mortality, extend survival time, and improve quality of life. We aimed to evaluate physical activity regimens in patients undergoing chemotherapy for ovarian cancer and analyze the factors influencing physical activity levels. Methods To facilitate the selection of patients with ovarian cancer hospitalized for chemotherapy in the Third Affiliated Hospital of Zhengzhou University and the First Affiliated Hospital of Zhengzhou University from August 2022 to February 2023, questionnaire surveys were conducted using the General Information Questionnaire, International Physical Activity Questionnaire, Hospital Anxiety and Depression Scale, and Revised Piper Fatigue Scale. Results Data were collected from 167 patients with ovarian cancer. Overall, 96 (57.5%) patients had low physical activity levels, 53 (31.7%) had moderate physical activity levels, and 18 (10.8%) had high physical activity levels. Logistic regression analysis revealed that sleep status, social support, anxiety, depression, and cancer-related fatigue were the main factors influencing physical activity in patients undergoing chemotherapy for ovarian cancer. Conclusions Physical activity levels of patients undergoing ovarian cancer chemotherapy were generally low. Therefore, healthcare professionals should pay greater attention to the physical activity in these patients. Targeted and individualized health guidance is recommended, and activity interventions should be implemented according to the influencing factors to promote disease understanding and increase physical activity levels.